Prostagladin D(2) is a mast cell-derived antiangiogenic factor in lung carcinoma - Murata, Takahisa (National Academy of Sciences, 2011)
It is well established that prostaglandins (PGs) are involved in tumor angiogenesis and growth, yet the role of prostaglandin D(2) (PGD(2)) remains virtually unknown. Here, we show that host hematopoietic PGD(2) synthase (H-PGDS) deficiency enhances Lewis lung carcinoma (LLC) progression, accompanied by increased vascular leakage, angiogenesis, and monocyte/mast cell infiltration. This deficiency can be rescued by hematopoietic reconstitution with bone marrow from H-PGDS–naive (WT) mice. In tumors on WT mice, c-kit(+) mast cells highly express H-PGDS. Host H-PGDS deficiency markedly up-regulated the expression of proangiogenic factors, including TNF-α in the tumor. In mast cell-null Kit(W-sh/W-sh) mice, adoptive transfer of H-PGDS–deficient mast cells causes stronger acceleration in tumor angiogenesis and growth than in WT mast cells. In response to LLC growth, H-PGDS–deficient mast cells produce TNF-α excessively. This response is suppressed by the administration of a synthetic PGD(2) receptor agonist or a degradation product of PGD(2), 15-deoxy-Δ(12,14)-PGJ(2). Additional TNF-α deficiency partially counteracts the tumorigenic properties seen in H-PGDS–deficient mast cells. These observations identify PGD(2) as a mast cell-derived antiangiogenic factor in expanding solid tumors. Mast cell-derived PGD(2) governs the tumor microenvironment by restricting excessive responses to vascular permeability and TNF-α production.